Evaluation for Distribution Medium Rice Policy in Kudus Regency - Suparno, Suparno; Pratomo, Setyohadi (Universitas Negeri Semarang, 2019)
The problem in this study is why the consumption of medium rice is smaller compared to premium rice. As is known in several Regency, the consumption pattern that usually occurs, medium rice consumption is greater than premium rice. The objectives of this study were: To identify patterns of rice consumption in Kudus Regency based on a survey approach; Analyzing the accuracy of survey data that has been collected so far through distribution surveys and consumption patterns based on the survey approach; Identify and analyze data from survey results on rice consumption patterns in Kudus Regency based on the survey approach. The research methodology uses a quantitative descriptive approach using simple statistical analysis. The method of data collection uses survey methods and data analysis using qualitative and quantitative analysis. The pattern of consumption of medium rice in Kudus Regency is lacking, because the people are more interested in or prefer to consume premium rice such as perfume and premium SS. The availability of rice in Kudus Regency when ordinary daily does not reflect the adequacy of availability because, during the survey, not all rice stocks have been recorded. The pattern of rice consumption in Kudus Regency follows the usual consumption pattern, which is sharply increased during religious holidays such as Idul Fitri and Christmas and New Year's Day. Economic factors influence the people pattern of rice consumption. The socio-economic level of the people is quite high, so they prefer to consume premium rice rather than medium. The price of rice, both medium and premium, fluctuated but was still under control. Rice price fluctuations follow market law, that is, if the high demand for rice stocks is limited, prices tend to rise. Vice versa, but the price of rice in Kudus Regency is still affordable by the community. Based on the survey results it can be recommended that the Department of Trade and Industry take the policy of distributing medium rice to certain locations, namely in the District of Dawe and Mojobo, where the level of consumption of medium rice is quite high.